2022
DOI: 10.4269/ajtmh.21-0782
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Challenges to COVID-19 Vaccination in the Darfur Region of Sudan

Abstract: The current COVID-19 pandemic has affected the ability of health systems to provide essential services globally. The Darfur region, located in the western part of Sudan, has been largely devastated by the war that began in 2003 and has been drawing considerable attention from the international community. The war, which erupted as a result of environmental, political, and economic factors, has led to tragic outcomes. Collapsing health-care infrastructures, health workforce shortages, lack of storage facilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Among them, VH and vaccine inequity are two major issues in the mass vaccination strategy for COVID‐19 control 46 . To some extent, VH and vaccine inequity are correlated with the local level of economy, health service, and production capacity 47 . An in‐depth understanding of people's attitude to booster shots would not only improve vaccination coverage in different regions but also increase incentives to expand production scale and develop a novel generation of vaccines for vaccine manufacturers, which will be helpful to reduce the social inequities and rehabilitate the social economy.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, VH and vaccine inequity are two major issues in the mass vaccination strategy for COVID‐19 control 46 . To some extent, VH and vaccine inequity are correlated with the local level of economy, health service, and production capacity 47 . An in‐depth understanding of people's attitude to booster shots would not only improve vaccination coverage in different regions but also increase incentives to expand production scale and develop a novel generation of vaccines for vaccine manufacturers, which will be helpful to reduce the social inequities and rehabilitate the social economy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our studies showed a higher actual vaccine coverage with at least one dose in Chinese DM patients (87.7%) compared with the study in India (21.4%) and Sudan (31.0%). The potential reason might be associated with the later investigation time in this study compared with others and the shortage of vaccination supply in India ( 28 ) and Sudan ( 29 ).…”
Section: Discussionmentioning
confidence: 85%
“…Challenges faced included vaccine scepticism due to distrust of the fast-paced vaccine development process [ 28 ], historical distrust in the formal healthcare system, fear of side effects, and misinformation [ 32 , 37 ]. A vaccination program in South Africa adopted the risk versus benefit approach in its communication strategy—acknowledging the rare chances of adverse vaccine reactions which are manageable but stressed on the higher probability of developing severe COVID-19 disease that can be life threatening and the key role of the vaccine in preventing it [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were logistical constraints in vaccine storage and transportation due to inadequate infrastructure, an inequitable spread of health facilities that excludes certain sub-populations from accessing care, and the short shelf life of vaccines [ 34 , 37 ]. The lack of timely data on COVID-19 vaccine safety and efficacy for pregnant women posed challenges to uptake in this population [ 29 ].…”
Section: Resultsmentioning
confidence: 99%